GLOBAL TESTING OF UNDER-MATCHED JOINTS - Praunseis, Zdravko; Marčič, Simon (Journal of Energy Technology, 2024)
The main aim of this experimental investigation was to determine whether the applied welding procedure for an under-matched welded joint with a soft root layer is appropriate for commercially available high strength low-alloyed steel. This steel usually requires preheating if a matching or overmatching weld consumable is used, which is not only expensive, but also needs a carefully designed and strictly followed welding procedure.
Keywords: under-matched joint; experiment; steel